Patterns of allergic sensitization and atopic dermatitis from 1 to 3 years: Effects on allergic diseases. Issue 1 (15th December 2017) - Dharma, C.; Lefebvre, D. L.; Tran, M. M.; Lou, W. Y. W.; Subbarao, P.; Becker, A. B.; Mandhane, P. J.; Turvey, S. E.; Sears, M. R.; ,
Summary: Background: While allergic sensitization and atopic dermatitis (AD) are known to increase the risk for allergic diseases, the impact of different temporal and clinical patterns of sensitization and AD is less well defined. Objective: We investigated patterns of sensitization and AD from early infancy to age 3, and the differential risk of developing allergic diseases within each pattern in a general cohort. Methods: Children (n = 2629) from the Canadian Healthy Infant Longitudinal Development (CHILD) Study underwent skin prick tests and were assessed clinically for AD at ages 1 and 3 years. We applied an unsupervised latent class analysis (LCA) to the following 5 factors at these ages: AD, food sensitization, inhalant sensitization, poly‐sensitization to foods and poly‐sensitization to inhalants. The risks for developing asthma, allergic rhinitis and food allergy at 3 years were evaluated for each identified group. Results: Five distinct classes were revealed by LCA: healthy (81.8%), atopic dermatitis (7.6%), inhalant sensitization (3.5%), transient sensitization (4.1%) and persistent sensitization (3.2%). Using healthy children as the baseline, children in the "atopic dermatitis" group had the next lowest risk for all allergic outcomes at 3 years; those in the "inhalant sensitization" group had the highest risk for allergic rhinitis; children in the "transient sensitization" group were at an increased risk for food allergy; while children in the "persistent sensitization" group had the highest risk for all allergic diseases. Conclusion and Clinical Relevance: There is substantial heterogeneity among allergen‐sensitized children. Researchers and clinicians need to be aware of the non‐specificity associated with labelling children simply as "atopic" and "non‐atopic" without considering the timing of their atopic history, type of sensitization and AD status. Children with AD who were poly‐sensitized to foods at an early age appear to be at greatest risk of developing other allergic diseases.